Effect of sintering temperature on structural and electrical properties of lead-free BNT–BT piezoelectric thick films. (July 2015) - Liu, Yantao; Ren, Wei; Zhao, Jinyan; Wang, Lingyan; Shi, Peng; Ye, Zuo-Guang
Abstract: Lead-free 0.94(Na0.5 Bi0.5 )TiO3 –0.06BaTiO3 (BNT–BT) piezoelectric thick films were fabricated by a tape casting method. The structural and electrical properties of BNT–BT thick films sintered at different temperatures from 1100 °C to 1180 °C were studied systematically. The X-ray diffraction result showed that all the thick films exhibited a perovskite phase. The increase of grain size of BNT–BT thick films could be observed clearly with increasing sintering temperature from SEM morphologies. It was found that with increasing sintering temperature, the roughness of the films increased from 139 nm to 285 nm, while the piezoelectric coefficient d 33 of the thick films increased monotonically in the range of 1100–1160 °C, and then decreased at 1180 °C. The maximum value of the piezoelectric coefficient d 33 was 112 pC/N at 1160 °C. At this sintering temperature, the dielectric constant and loss tangent were 1928 and 5.29% at 1 kHz, while the values of the remnant polarization and the coercive field were 26.3 μC/cm 2 and 27.1 kV/cm, respectively. The piezoresponse force microscopy was used to study the piezoelectric behaviors of BNT–BT thick films, which revealed both single domain and layered multi-domain in the grains.